Task switching involves working memory: Evidence from neural representation - Wang, Yanqing; Zhou, Xing; Peng, Xuerui; Hu, Xueping (Frontiers in Psychology, 2022)
It is generally assumed that task switching involves working memory, yet some behavioral studies question the relationship between working memory and task-switching ability. This debate can be resolved by directly combining the brain activity pattern in task switching and working memory processes. If the task switching involves working memory, the neural activity patterns evoked by such two tasks would exhibit higher similarity. Here, we employed the task switching task and working memory to investigate the characteristic of the neural representation in such two cognitive processes. A conjunction analysis showed that the bilateral superior parietal lobule(SPL), bilateral insula, bilateral middle frontal gyrus(MFG), bilateral dorsal lateral prefrontal cortex(DLPFC) and pre-supplementary motor area (pre-SMA) were commonly and significantly activated in both task switching and working memory task. Critically, we found that task switching and working memory processing elicited similar activity patterns in bilateral SPL, right insula, left MFG, left DLPFC and pre-SMA, consistent with common neural processes for both tasks. These results not only suggest that the task switching process involves working memory from the perspective of neural representation, but also provide major new insights into the neurocognitive links between task switching and working memory.